Modulation of Cell Surface Protein Free Thiols: A Potential Novel Mechanism of Action of the Sesquiterpene Lactone Parthenolide - Skalska, Jolanta; Brookes, Paul S.; Nadtochiy, Sergiy M.; Hilchey, Shannon P.; Jordan, Craig T.; Guzman, Monica L.; Maggirwar, Sanjay B.; Briehl, Margaret M.; Bernstein, Steven H. (PLOS ONE, 2009)
Background There has been much interest in targeting intracellular redox pathways as a therapeutic approach for cancer. Given recent data to suggest that the redox status of extracellular protein thiol groups (i.e. exofacial thiols) effects cell behavior, we hypothesized that redox active anti-cancer agents would modulate exofacial protein thiols. Methodology/Principal Findings To test this hypothesis, we used the sesquiterpene lactone parthenolide, a known anti-cancer agent. Using flow cytometry, and western blotting to label free thiols with Alexa Fluor 633 C5 maleimide dye and N-(biotinoyl)-N-(iodoacetyl) ethylendiamine (BIAM), respectively, we show that parthenolide decreases the level of free exofacial thiols on Granta mantle lymphoma cells. In addition, we used immuno-precipitation techniques to identify the central redox regulator thioredoxin, as one of the surface protein thiol targets modified by parthenolide. To examine the functional role of parthenolide induced surface protein thiol modification, we pretreated Granta cells with cell impermeable glutathione (GSH), prior to exposure to parthenolide, and showed that GSH pretreatment; (a) inhibited the interaction of parthenolide with exofacial thiols; (b) inhibited parthenolide mediated activation of JNK and inhibition of NFκB, two well established mechanisms of parthenolide activity and; (c) blocked the cytotoxic activity of parthenolide. That GSH had no effect on the parthenolide induced generation of intracellular reactive oxygen species supports the fact that GSH had no effect on intracellular redox. Together these data support the likelihood that GSH inhibits the effect of parthenolide on JNK, NFκB and cell death through its direct inhibition of parthenolide's modulation of exofacial thiols. Conclusions/Significance Based on these data, we postulate that one component of parthenolide's anti-lymphoma activity derives from its ability to modify the redox state of critical exofacial thiols. Further, we propose that cancer cell exofacial thiols may be important and novel targets for therapy.